KEWENANGAN ABSOLUT PERADILAN AGAMA DI INDONESIA PADA MASA KOLONIAL BELANDA HINGGA MASA PASCA REFORMASI - Abdullah Tri Wahyudi (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2016)
This article discusses the absolute competencies of the Religious Court in Indonesia since the Dutch colonial era until the Reformation. It aims at surveying the history and development of the Court as well as its competencies. Using historical perspective this article portrays the topic in chrocological order.